2020
DOI: 10.1002/aic.16941
|View full text |Cite
|
Sign up to set email alerts
|

Determination method of the cavern boundary viscosity in a stirred tank with pseudoplastic fluid

Abstract: It is essential to predict the cavern boundary accurately for investigating the cavern characteristics and achieving efficient mixing of the pseudoplastic fluids. The distribution characteristics of apparent viscosity of xanthan gum solutions at different mass concentrations stirred by the impeller of perturbed six-bent-bladed turbine (6PBT impeller) were numerically investigated through the computational fluid dynamics (CFD) simulation based on laminar flow model. The determination method of the cavern bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The average shear rate can be gained in accordance with Metzner and Otto′s correlation γ̇ avg = k normals N …”
Section: Physical Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…The average shear rate can be gained in accordance with Metzner and Otto′s correlation γ̇ avg = k normals N …”
Section: Physical Systemmentioning
confidence: 98%
“…For radial flow impeller, k s = 11.5. 26,28,29 The apparent viscosity (η) of the xanthan gum solution can be expressed as 24−26…”
Section: Physical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, many investigations have focused on the mixing characteristics of different non-Newtonian fluids. [27][28][29][30][31][32] Jegatheeswaran and Ein-Mozaffari 33 found that it is possible to cut the energy consumption while enhancing the aeration efficiency at low Reynolds numbers in a Scaba-anchor coaxial mixer involving power-law fluids. Ramsay et al 34 characterized the mixing of Newtonian and viscoelastic fluids in batch tanks with "butterfly" impellers and found that the laminar constant was equal to 122 and the Metzner-Otto constant was equal to 16.0, and the two constants are closely related to the correlation of power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Since the viscosity of non‐Newtonian fluids depends on the shear rate, some problems such as complex flow, 20,21 formation of dead zones, 22–24 low mixing efficiency, and considerable energy consumption 25,26 arise in the mixing process. Hence, many investigations have focused on the mixing characteristics of different non‐Newtonian fluids 27–32 . Jegatheeswaran and Ein‐Mozaffari 33 found that it is possible to cut the energy consumption while enhancing the aeration efficiency at low Reynolds numbers in a Scaba‐anchor coaxial mixer involving power‐law fluids.…”
Section: Introductionmentioning
confidence: 99%